Viscometric Evaluation and Micellar Properties of Cu (II) Soap Derived from Neem Oil in Non-aqueous Media - Khan, Shema; Sharma, Rashmi; Sharma, Arun K. (Current Physical Chemistry, 2018)
Background: The Colloidal-chemical behavior of Copper surfactants are gaining popularity on account of their utilitarian effect such as foaming, emulsification and fungicidal activities. The studies of various parameter derived from viscometric equations provide revealing interpretations of solute - solvent interaction and structural insight of micelle in binary and ternary system, which plays a vital role in its selection for industrial and biological applications. Objective: It is plan to study viscosity of copper neem soap solutions in benzene plus methanol mixture in different composition in order to understand the nature of critical micelle concentration and micellar characterization. Method: First we synthesized copper neem soap based upon their widest applicability performa. It was characterized by elemental analysis, melting points, IR, NMR, spectral studies. Benzene-methanol has been selected as co- solvents since mixed solvents show tendency to interact with complex molecules and result in affecting the aggregation of soap molecule. Results: The results were used to determine the Critical Micelle Concentration (CMC), soap complex-solvent interactions and the effect of chain length of the surfactant molecule on various parameters. The results with regard to solute-solute and solute- solvent interaction have been discussed in terms of well-known Moulik's and Jones- Dole equations. The effect of surfactant concentration on viscosity of the solution in non-polar solvent has been discussed. Conclusion: The viscosity parameters are important to understand the colloidal behavior, CMC characteristics and nature of the complexes. These studies indirectly help in identifying the structural insight, physical and biochemical properties of above metallic soaps. The above studies will definitely help future researchers to apply these novel soaps in multiple interlinked fields based on their widest applicability. Overall, the present course of study helps us to understand the characteristic nature and application of biological active copper soaps.
Keywords: odour